Budaya Malu dan Penegakan Konstitusi Indonesia: Telaah Kritis atas Peran Mahkamah Konstitusi sebagai Pelindung Konstitusi - Mahardika, Agus; Wisnu, Bagas; Arthaleza, Fergie Brillian; Viano, Nurloise; Abdallah, Raffi Ikzaaz; Hendarwin, Rasendriya; Ramadhan, Raihan; Hagina, Rizki; Febrian, Matthew (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study examines the shame culture phenomenon in the context of constitutional enforcement in Indonesia, particularly through a critical lens on the Constitutional Court Decision Number 90/PUU-XXI/2023. The research investigates the transformation of the Constitutional Court's role from merely a negative legislator to a positive legislator, along with its ethical and constitutional implications. The research method used is normative juridical with conceptual and case approaches. The results indicate the subordination of shame culture to political interests in Constitutional Court decision-making, which potentially degrades the values of constitutionalism and judicial ethics. This study concludes that strengthening shame culture within constitutional judicial institutions is an urgent need to re-establish the constitution's dignity as an instrument for limiting power and preventing authoritarianism. Research recommendations include reforming the selection mechanism for constitutional judges, strengthening judicial codes of ethics, and increasing public participation in constitutional judicial oversight.